Identification and quantification of amino acids and related compounds based on Differential Mobility Spectrometry. Issue 14 (1st June 2020) - Berthias, Francis; Wang, Yali; Alhajji, Eskander; Rieul, Bernard; Moussa, Fathi; Benoist, Jean-François; Maître, Philippe
Abstract : A new metabolite descriptor allowing fast quantification for the diagnosis of metabolic diseases. Abstract : Amino acids and related compounds constitute a class of biomarkers which is analyzed for early diagnosis of metabolic diseases (MDs). Protocols based on liquid chromatography hyphenated to tandem mass spectrometry (LC-MS/MS) are routinely used for MD diagnosis. Our ultimate objective is to evaluate the analytical performance of differential mobility spectrometry (DMS) hyphenated to MS/MS, in the perspective of using DMS-MS/MS as an alternative or complementary method for the topics of emergency in metabolic diagnosis and newborn rapid screening. The aim of the present study is to evaluate the robustness of a DMS-MS/MS protocol for the separation, identification, and quantification of amino acids and related compounds. Performance in terms of peak capacity and separation of isobaric and isomeric species is compared to those using drift tube type ion mobility spectrometry instruments. High reproducibility of the measurement of the DMS compensation voltage (CV) of metabolites shows that this CV parameter, or the corresponding electric field, could be used for application in metabolite identification. Multiple measurements show that the CV value of each AA or related compound is stable over a large period of time (6 months). Potential effects of matrix or concentration of the analytes on the DMS identifier are found to be negligible. Quantification of a selected set of metabolites in human plasmas has been carried out. The method linearity, intra-assay and inter-assay precision, detection limit, quantification limit and trueness analysis were assessed as adequate for both physiological and pathological conditions. Concentration levels of metabolites derived with our DMS-MS protocols were found to be in good agreement with those obtained with routine LC-MS/MS protocols used for the diagnosis of MDs at the Hospital Robert Debré (Paris).